Anterior cruciate ligament injury risk in sport: A systematic review and meta-analysis of injury incidence by sex and sport classification - Montalvo, A. M.; Schneider, D. K.; Webster, K. E.; Yut, L.; Galloway, M. T.; Heidt, R. S. Jr.; Kaeding, C. C.; Kremcheck, T. E.; Magnussen, R. A.; Parikh, S. N.; Stanfield, D. T.; Wall, E. J.; et al. (Journal of Athletic Training, 2019)
Objective To evaluate sex differences in incidence rates (IRs) of anterior cruciate ligament (ACL) injury by sport type (collision, contact, limited contact, and noncontact).